Basal cell carcinoma of the vulva - Galdós H., Ricardo (2015)
Basal cell carcinoma of the vulva is a very rare lesion, and occupies the fourth place in the total of malignant tumors of the vulva attended at the Instituto Nacional de Enfermedades Neoplasicas of Lima, with an incidence of 2,7 per cent. The simple vulvectomy is the most adequate from of therapy when the basal cell carcinoma is present by itself, i.e. pure. The radical vulvectomy and bilateral regional node dissection must be practiced in all cases of basal squamous cells lesions.